TMIC-18. ROLE OF DISCOIDIN DOMAIN RECEPTORS (DDR1/DDR2) IN SENSITIZATION OF GLIOMAS TOWARDS RADIOTHERAPY. (14th November 2022) - Syed, Mohammad Faisal; Comba, Andrea; Varela, Maria Luisa; Argento, Anna; Brumley, Emily; Abel, Clifford; Castro, Maria; Lowenstein, Pedro
Abstract: Glioblastoma (GBM), a high-grade glial tumor, is highly aggressive and is characterized by intra-tumoral heterogeneity and widespread infiltration, impairing therapeutic success. Our laboratory discovered dynamic multicellular fascicles of spindle-like and aligned cells with mesenchymal features called "oncostreams" inside GBM tumors that facilitate invasion into the normal brain. We found that collagen 1α1 (Col1A1) is essential for oncostream structure and function. Using in vivo intravital imaging and ex vivo explant glioma models, we established that Col1A1 suppression abolishes oncostreams, reprograms the malignant histopathological phenotype, and extends median survival in mice. However, the signaling through which collagen communicates to maintain an invasion-permissive glioma tumor microenvironment remains unclear. We propose to analyze a poorly understood collagen receptor family -the discoidin domain receptors (DDRs) - which is expressed in glioma and perivascular stromal cells. The Cancer Genome Atlas (TCGA) and Chinese Glioma Genome Atlas (CGGA) data suggest DDR1/DDR2 overexpression correlates with tumor progression and poor prognosis in glioma patients. Our RNA-seq data further confirm overexpression of DDRs in NPA and NPD glioma compared to the normal brain. Our preliminary data suggests that inhibiting collagen receptors DDR1 or DDR2 sensitizes glioma cells to radiotherapy (IR). DDR1 inhibition completely disrupts oncostreams` structure in the ex vivo explant glioma model. Moreover, pharmacological inhibition of DDR1 combined with irradiation significantly enhances the median survival of NPA (Nras, shP53, shATRX) tumors in an orthotopic mouse glioma model. Furthermore, we are currently testing whether inhibition of DDR1 using a genetically engineered mouse model (GEMM) of glioma called NPAD1 (Nras, shP53, shATRX, shDDR1) will show an increase in overall survival. We hypothesize that blocking collagen receptors DDR1 or DDR2 will control tumor growth, invasion and mediate anti-glioma immunity. This study will eventually uncover a novel therapeutic treatment for GBM, targeting DDR1 and DDR2 in human patients.